A Novel Deinococcus Antioxidant Peptide Mitigates Oxidative Stress in Irradiated CHO-K1 Cells - Sangyong Lim; Ha-Yeon Song; Hae Ran Park; Ki Bum Ahn (Microorganisms)
Reactive oxygen species (ROS), byproducts of cellular metabolism and environmental factors, are linked to diseases like cancer and aging. Antioxidant peptides (AOPs) have emerged as effective countermeasures against ROS-induced damage. The Deinococcus genus is well known for its extraordinary resilience to ionizing radiation (IR) and possesses complex antioxidant systems designed to neutralize ROS generated by IR. In this study, we developed four peptides, each containing 9 to 11 amino acids, from the leaderless mRNA (lmRNA) sequences of D. deserti. Lacking a 5′ untranslated region, lmRNAs directly initiate protein synthesis, potentially encoding small peptides such as AOPs. Of the four peptides, Ddes-P3 was found to exhibit significant antioxidant capabilities in vitro, effectively scavenging ABTS radicals. Ddes-P3 provided considerable defense against IR-induced oxidative stress in CHO-K1 cells, demonstrating a notable reduction in ROS production and lipid peroxidation. The peptide’s potential was highlighted by its ability to enhance cell survival and maintain mitochondrial membrane potential under irradiative stress, suggesting its utility as a nontoxic and effective radioprotector in mitigating radiation-induced cellular damage. This study explores the potential role of lmRNA in synthesizing AOPs within Deinococcus. Identifying lmRNAs that encode AOPs could deepen our understanding of their cellular resistance to oxidative stress and pave the way for creating innovative biotechnological and therapeutic AOPs.